THE EDUCATION OF UMY STUDENTS IN RURAL CLINICS - Dr.drg. Tita Ratya Utari, Sp.Ort (Faculty of Dentistry Thammasat University, 2013)
the purpose this program is that students can apply the knowledge in an integrated dental. helath to solve oral helath problems in the community, perform dental and oral health services independently and in accordiance with evidence-based and responsible for the work